La caravane des animaux. Circulation des « orangs-outans » et des savoirs, reconfigurations des frontières de l’humain - Silvia Sebastiani (Diasporas: Circulations, Migrations, Histoire)
This article investigates the presence of exotic animals in Enlightenment Britain, paying particular attention to the “orangutans”. It traces the mobility of these beasts and the long-distance networks of their circulation; it outlines the multiple spaces of sociability around their observation while stressing the diverse registers of discourses of which they are objects. Placed at the heart of comparative anatomy since the end of the 17th century, the orangutans became one of the great attractions in the new public spaces offered by London coffee-houses. The spectacularisation of the primates offered to a wider eighteenth-century public a new object for reflection about humanity and its boundaries.